Pain and moderate to vigorous physical activity in adolescence: an international population-based survey - Swain, Michael; Henschke, Nicholas (Pain medicine, 2016)
To evaluate whether individual types of pain (headache, stomach-ache, and backache) or multiple pains affect the odds of young people achieving the recommended 60 minutes of moderate to vigorous physical activity (MVPA) per day in a large representative sample